Đối tượng điều chỉnh của Luật Hiến pháp - Dung, Nguyễn Đăng (VNU Journal of Science: Social Sciences and Humanities; Vol 15 No 1, 1999)
Tóm tắt By analyzing the deficiency of traditional views of Constitutional Law the author has suggested new viewpoint about the subject of Constitutional Law. It is the branch of legal system regulating the political regime of each nation. Moreover, the author also proposes that it is impossible to consider the Constitutional Law as the main branch of legal system